THE ROLE OF STATE PROGRAMS IN THE DEVELOPMENT OF ENERGY INFRASTRUCTURE (Економіка і регіон/ Economics and region, 2025)
THE ROLE OF STATE PROGRAMS IN THE DEVELOPMENT OF ENERGY INFRASTRUCTURE
Keywords: державні програми; енергетика; інфраструктура; сталий розвиток; уряд; енергетичний сектор; джерела енергії; відновлювана енергетика